Mechanisms and influencing factors of cataract occurrence or progression after vitrectomy - Miao Zhang (Press of International Journal of Ophthalmology (IJO PRESS), 2021)
Since first proposed by O'Malley in 1972, the revolutionary vitrectomy has brought ophthalmic surgery into a new era, bringing hope to countless patients with vitreoretinal diseases. With the development of surgical techniques, increased safety and effectiveness, and expanded surgical indications, vitrectomy has become the most common surgical treatment for various posterior segment diseases. Though there is a trend of decreasing in postoperative complications, the occurrence and progression of cataract remains the most common complication after vitrectomy. As cataract would compromise the postoperative vision and fundus observation, cataract extraction surgery is always inevitable, which seriously increases the burden of patients. The pathogenesis of cataract is till inconclusive. There are currently many hypotheses including increased oxygen partial pressure around the lens, destruction of the vitreous structure, and phototoxicity. This article reviews the incidence, mechanism and influencing factors of cataract occurrence or progression after vitrectomy, aiming to provide more evidence for further investigation of pathogenesis, prevention and treatment for post-vitrectomy cataract.